Neuroproteins in Cancer: Assumed Bystanders Become Culprits. Issue 14 (5th June 2018) - Li, Xiang; Dun, Matt D.; Faulkner, Sam; Hondermarck, Hubert
Abstract: Recent breakthrough discoveries have highlighted the stimulatory role of nerves in cancer initiation and progression, through the release of neurotransmitters and growth factors by nerve terminals in the tumor microenvironment. Intriguingly, neuroproteins such as neuronal membrane proteins, synaptic proteins, neurotransmitters, and neurotrophic growth factors as well as their corresponding receptors, to name only a few, are frequently found in proteomic analyses of cancer tissues external to the brain and central nervous system. While the usual explanation was that neuroproteins were actually not specific to the nervous system and were therefore also expressed in cancer cells, it now appears that the presence of neuroproteins in cancer is largely due to the infiltration of nerves in the tumor microenvironment. Given the newly identified function of nerves as promoters of cancer growth and metastasis, neuroproteins should be considered with great attention because they may actually represent innovative biomarkers and therapeutic targets in oncology.